2011
DOI: 10.4276/030802211x13046730116533
|View full text |Cite
|
Sign up to set email alerts
|

Appreciative Inquiry in Occupational Therapy Education

Abstract: The background to this study is the growing literature on the potential of applying appreciative inquiry (AI), commonly associated with business, to health care. As AI encourages creative thinking and is based on considering what can be done as opposed to what cannot, it seems suitable for educating occupational therapy students. To date, just one school of occupational therapy in the United Kingdom is known to have incorporated AI into its problem-based learning programme, whereby students are encouraged to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…to think of what can be done instead of what cannot. As Rubin, Kerrel, and Roberts (2011) in their study of occupational therapy education concluded, both full-time occupational therapy students and teachers enjoyed using the AI approach. AI encourages thinking positively and looking at the situation through an enabling lens.…”
Section: Overall Effectiveness Of the Education Programmentioning
confidence: 99%
“…to think of what can be done instead of what cannot. As Rubin, Kerrel, and Roberts (2011) in their study of occupational therapy education concluded, both full-time occupational therapy students and teachers enjoyed using the AI approach. AI encourages thinking positively and looking at the situation through an enabling lens.…”
Section: Overall Effectiveness Of the Education Programmentioning
confidence: 99%
“…Downing et al (2011) suggested that PBL enhanced students' ability to problem solve and to reason clinically, and Reeves et al (2004) maintained that metacognitive skills (like clinical reasoning), which occupational therapy students acquire through participating in PBL, mirror the skills needed for professional practice. Barrett (2010) and Rubin et al (2011) focused on students' involvement in PBL group work and the creative approaches used by students to address problem-based scenarios.…”
Section: Students' Experiences Of Problem-based Learning and Knowledgementioning
confidence: 99%
“…Therefore, in order to change an organisation, one must act on the way individuals interpret the organisation (Cooperrider and Srivastva, 1994). Whereas in the beginning the appreciative inquiry was used in organizational development (Cooperrider & Srivastva, 1987;Cooperrider & Srivastva, 1994;Cooperrider & Whitney, 2001;Cooperrider & Avital, 2004;Rattanaphan, 2010;Bushe, 2010), this strategy of change management has gradually expanded towards areas such as education (Yballe & O'Connor, 2000;Lander, 2002;Kumar & Chacko, 2010;Kelly, 2010;Bradu & Sandu, 2008, Cojocaru, 2011, healthcare (Hirunwat, 2011;Rubin, Kerrell, & Roberts, 2011), evaluation (Coghlan, Preskill & Catsambas, 2003;Cojocaru, 2008;Messerschmidt, 2008;Ojha, 2010;Kavanagh et al, 2010), therapy (Sandu & Ciuchi, 2010;Donaldson & Ko, 2010;Rubin, Kerrell & Roberts, 2011;Galazka, 2011;Wendt, Tuckey & Prosser, 2011), education (Kumar & Chacko, 2010;Kelly, 2010;Cojocaru, 2011), research methodology (Cojocaru, 2005;Reed, 2007;Kluger & Nir, 2010;Van Gramberg, 2010;Cowling & Repede, 2010), leadership in organizations (Ludema, Whitney, Mohr & Griffi n, 2003;Bushe & Kassam, 2005;Hart, Conklin & Allen, 2008). Our aim was to see to what extent the appreciative inquiry could be applied in various social work practices …”
Section: Literature Reviewmentioning
confidence: 99%